Development and Validation of Usability Heuristics for Evaluation of Interfaces in ATMs - Chanco, Cristhian (2019)
ATM systems are part of the devices that have more managed approach and facilitate the use of financial services for people. However, on occasions, displayed interfaces can be frustrating to use. Usability is a principle that contemplates such situations, so it is necessary to have appropriate tools to evaluate ease of use on the products. For this reason, we present a revised version of eighteen usability heuristics proposed for ATM applications. In this paper, we describe the process that is followed from the collection of information, creation of the heuristic set, validation and refinement.